Carbon nanotube–polyaniline core–shell nanostructured hydrogel for electrochemical energy storage1. Issue 48 (28th May 2015) - Chen, Po-Yen; Dorval Courchesne, Noémie-Manuelle; Hyder, Md Nasim; Qi, Jifa; Belcher, Angela M.; Hammond, Paula T.
<x xml:space="preserve">Abstract</x> Highly porous three-dimensional core (carbon nanotube)–shell (polyaniline) conductive hydrogels synergize the advantageous features of hydrogels and conductive materials, showing enhanced electrical conductivity and electrochemical activity.